Post‐operative survival following metastasectomy for patients receiving BRAF inhibitor therapy is associated with duration of pre‐operative treatment and elective indication. Issue 8 (17th June 2015) - He, Mike; Lovell, Jane; Ng, Bee Ling; Spillane, John; Speakman, David; Henderson, Michael A.; Shackleton, Mark; Gyorki, David E.
Abstract Introduction Metastasectomy can provide durable disease control for selected patients with metastatic melanoma. Vemurafenib is a BRAF kinase inhibitor which has demonstrated significant improvement in disease‐specific survival in patients with metastatic melanoma with a BRAF gene mutation. This study examined the efficacy and safety of metastasectomy during treatment with vemurafenib. Methods A retrospective review was performed of all patients receiving vemurafenib at Peter MacCallum Cancer Centre. Patient records were reviewed to identify patients undergoing surgery within 30 days of vemurafenib therapy. Descriptive statistics and survival analysis were performed. Results Nineteen patients underwent 21 metastasectomies including craniotomy (57%), spinal decompression (14%), small bowel resection (14%), lung resection (9.5%) and neck dissection (4.5%). Indications for surgery were: an isolated residual focus of disease (n = 2); isolated progressive disease in the setting of stability elsewhere (n = 9); and symptomatic disease (n = 8). Grade 2 or higher surgical complications occurred in 19% of cases and there was one peri‐operative death. Median post‐operative survival was seven months. There was a trend toward improved post‐operative survival for patients with longer duration of vemurafenib therapy (P = 0.04) and for those undergoing elective surgery (P = 0.07). Conclusion Resection of oligometastatic disease during BRAF‐targeted therapy is safe. Selected patients have durable post‐operative disease control. J. Surg. Oncol. 2015 111:980–984. © 2015 Wiley Periodicals, Inc.